Vermicompost and zeolite improve yield, nutrient uptake, essential and fixed oil production, and composition of Nigella sativa L. - Rahmani, Roghayeh; Khalesro, Shiva; Heidari, Gholamreza; Mokhatssi-Bidgoli, Ali (Frontiers in Sustainable Food Systems, 2023)
The exogenous application of organic and natural inputs is a key strategy for producing healthy and high-quality crops in sustainable agricultural systems. Black cumin (Nigella sativa L.) is a highly popular plant used worldwide in the medical and food industries. According to the authors' knowledge, no research has been published to examine the effects of zeolite and vermicompost on yield components, nitrogen (N), phosphorous (P), and potassium (K) contents in seeds, essential and fixed oil contents, or the composition of black cumin in the organic agricultural system. In a semi-arid area of Iran in 2017 and 2018, an experiment with a full factorial layout was conducted using a randomized complete block design with three replications. The experimental treatments included four vermicompost rates (0, 2, 4, and 6 tons ha−1) and four zeolite rates (0, 3, 6, and 9 tons ha−1). There were linear responses between either vermicompost or zeolite application rates and the majority of the attributes studied. The integrated treatment of 6 tons of vermicompost and 9 tons of zeolite ha−1 produced the maximum seed and biological yields (466.2 and 3716.7 kg ha−1, respectively). The utilization of 6 tons of vermicompost ha−1 increased the N, P, and K contents of seed by 13.5%, 10.8%, and 14.1%, respectively, compared with the control. Seed essential oil content was enhanced by 24.1% in plots treated with 9 tons of zeolite ha−1 compared to the untreated control. The use of 6 tons of vermicompost ha−1 resulted in higher production of unsaturated fatty acids such as linoleic (53.3%), oleic (25.36%), and linolenic acid (0.6%) in oil. Overall, both the quantity and quality of black cumin improved when vermicompost and zeolite were used for 2 consecutive years. This showed the agronomic potential of both amendments in promising and environmentally friendly agricultural systems.